Parent opinions on the individualisation of education of children with autism spectrum disorders at schools - Kulešė, Živilė; Kaffemanienė, Irena (Special Education, 2020)
The article examines the opinions of parents raising children with ASD about the individualisation of their children’s education at schools. A theoretical analysis of the relevance of the partnership of parents raising children with ASD with teachers and possibilities of their participation in the process of institutional education of their children has been carried out; special educational strategies for children with ASD and opportunities for individualisation of education in general education schools were reviewed. The empirical study was performed by the method of questionnaire survey of the parents (N = 104) raising children with ASD; the methods of descriptive statistics were used to analyse quantitative data. The answers to the open-ended questions were examined using qualitative and quantitative content analysis.